Spin-phonon coupling parameters from maximally localized Wannier functions and first-principles electronic structure: Single-crystal durene - Sanvito, Stefano; Roychoudhury, Subhayan (My University, 2018)
Spin-orbit interaction is an important vehicle for spin relaxation. At finite temperature lattice vibrations modulate the spin-orbit interaction and thus generate a mechanism for spin-phonon coupling, which needs to be incorporated in any quantitative analysis of spin transport. Starting from a density functional theory ab initio electronic structure, we calculate spin-phonon matrix elements over the basis of maximally localized Wannier functions. Such coupling terms form an effective Hamiltonian to be used to extract thermodynamic quantities, within a multiscale approach particularly suitable for organic crystals. The symmetry of the various matrix elements is analyzed by using the Γ-point phonon modes of a one-dimensional chain of Pb atoms. Then the method is employed to extract the spin-phonon coupling of solid durene, a high-mobility crystal organic semiconductor. Owing to the small masses of carbon and hydrogen spin orbit is weak in durene and so is the spin-phonon coupling. Most importantly, we demonstrate that the largest contribution to the spin-phonon interaction originates from Holstein-like phonons, namely, from internal molecular vibrations.
PUBLISHED
Keywords: Electron-phonon coupling; Electronic structure; Organic electronics; Spin diffusion; Spin relaxation; Spin-orbit coupling; Spintronics; Organic semiconductors